Sustainable urban development in the European Union : a framework for action (COM(98)605). (Office for Official Publications of the European Communities, 1999)
In 1997 the Commission adopted the Communication "Towards an Urban Agenda in the European Union". The Commission indicated its intention to examine EU policies from the point of view of their urban impact and to improve policy integration at urban level. Reactions from EU institutions, the Ministers of Regional Policy and Spatial Planning at their informal meetings and outside organisations have been very urged to take further steps. This publication (COM(98)605 28.10.1998) presents the EU Framework for action for sustainable urban development which aims at better coordinated and targeted community action for urban problems and is organised under four interdependent policy aims: strengthening econmiv prosperity and employment in towns and cities.- promoting equality, social exclusion and regeneration in urban areas.- protecting and improving the urban environment.- contributing to good urban governance and local empowerment.